Sepsis-associated mortality in England: an analysis of multiple cause of death data from 2001 to 2010. Issue 8 (2nd August 2013) - McPherson, Duncan; Griffiths, Clare; Williams, Matthew; Baker, Allan; Klodawski, Ed; Jacobson, Bobbie; Donaldson, Liam
Abstract : Objectives: To quantify mortality associated with sepsis in the whole population of England. Design: Descriptive statistics of multiple cause of death data. Setting: England between 2001 and 2010. Participants: All people whose death was registered in England between 2001 and 2010 and whose certificate contained a sepsis-associated International Classification of Diseases, 10th Revision (ICD-10) code. Data sources: Multiple cause of death data extracted from Office for National Statistics mortality database. Statistical methods: Age-specific and sex-specific death rates and direct age-standardised death rates. Results: In 2010, 5.1% of deaths in England were definitely associated with sepsis. Adding those that may be associated with sepsis increases this figure to 7.7% of all deaths. Only 8.6% of deaths definitely associated with sepsis in 2010 had a sepsis-related condition as the underlying cause of death. 99% of deaths definitely associated with sepsis have one of the three ICD-10 codes—A40, A41 and P36—in at least one position on the death certificate. 7% of deaths definitely associated with sepsis in 2001–2010 did not occur in hospital. Conclusions: Sepsis is a major public health problem in England. In attempting to tackle the problem of sepsis, it is not sufficient to rely on hospital-based statistics, or methods of intervention, alone. A robust estimate of the burden of sepsis-associated mortality in England can be made by identifying deaths with one of the three ICD-10 codes in multiple cause of death data. These three codes could be used for future monitoring of the burden of sepsis-associated mortality.